Falsafah dan Sistem Pendidikan: Perbandingan Antara Plato dan Ibn Sina - Zakaria, Idris (Afkar: Jurnal Akidah dan Pemikiran Islam, 2000)
Education is an important mechanism in building human civilization. This article focuses on the philosophy and the system of education as proposed by Plato in his The Republic and The Laws as well as Ibn Sina in his Kitab al-Siyasa.